Sigurverkið - Arnaldur Indriðason 1961- (Vaka-Helgafell, 2021)
Iceland's bestselling author and many times rewarded, Arnaldur Indriðason, here delivers a historical novel. Taking place in the southern Western fjords and Copenhagen in the seventeenth century, it tells the story of working class people of the time that were bound to their masters and household. This is Arnaldur's twenty fifth novel and long may he continue.